ANALISIS KONSEP ETIKA, NORMA, DAN HUKUM DALAM IMPLEMENTASI HUKUM EKONOMI SYARIAH - Sulistiyo, Budi; Anwar, Syahrul; Kania, Dede; Faturokhman, Aziz (CV. Strata Persada Academia, 2023)
This research analyzes in depth the complex relationship between ethics, norms and law in the context of implementing Sharia Economic Law. This research uses qualitative methods with descriptive analysis studies through library literature where study sources include books, journals and the internet that are relevant to the research object. Through structured research methods, this research investigates how understanding Islamic ethics influences the norms that apply in Islamic financial practices and the important role of law in ensuring compliance with Sharia principles in every transaction and economic activity. The results of this research are that, in this domain, the main elements that form the basis of Islamic Economic Law are ethics, norms and law. Islamic ethics, which emphasizes integrity, justice, and social responsibility as core values, provides a moral foundation for action in economic activities. On the contrary, social and cultural norms, including the prohibition of usury and the principle of caution in investment, have an important role in guiding Islamic economic behavior. Law, in this context, is the formal framework that regulates and ensures compliance with Sharia principles. This includes regulations implemented by authorized institutions and enforced through the judicial system.